UPAYA PENINGKATAN KINERJA APARATUR PEMERINTAH YANG PROFESIONAL DALAM MENUJU GOOD GOVERNANCE - Rusli (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2019)
Many parties talk about bureaucracy good governance, especially for developing countries that are working hard to carry out development in various sectors of people's lives. Many views and opinions were raised to create good public governance. Of course these efforts are not easy to implement as well as building a physical facility, a building for example, which can be estimated with certainty of the materials and the completion of the building. The construction of state administration cannot be built as easily and quickly as the construction of the building. Even in the current era of globalization, the state administration system is also related and influenced by international developments through the Asia Pacific Economic Cooperation (APEC) and World Trade Organization (WTO) forums. Commitment to include and provide opportunities for the community to participate in development. This is important, because without this commitment, what arises is not community participation but antipathy and dislike in the behavior and wisdom of the government apparatus. At the same time, in the government apparatus or bureaucracy will grow slowly but surely domineering attitudes, perceptions or feelings most know, most can, which ultimately lead to arrogance of government bureaucracy. The state administration system or government bureaucracy is an open system. Therefore the problems, although they should not, which exist within the bureaucracy cannot be separated from the influence of other systems outside the government bureaucracy. The role and function of the government apparatus must be returned as state servants and public servants, who have always been forgotten. As state servants and public servants, the government apparatus must be responsive, proactive and prioritize the interests of many people and not serve personal interests, groups, ruling parties, or parties that become their idols.